ANALISIS INTERAKSI SOSIAL ANAK BERKEBUTUHAN KHUSUS (ABK) MELALUI PROGRAM PEER FRIENDS DI SD NEGERI 1 LOSARI - Dilla Nur Aziza; Dwi Rahayu; Wulan Trisnawaty (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Positive social interaction is an important component in the implementation of inclusive education. However, its implementation still faces various obstacles that have an impact on communication and social relations of ABK students. This study aims to analyze the social interaction of ABK students through the Peer Friends Program at SD Negeri 1 Losari, using a descriptive qualitative approach, with research subjects, namely school principals, Special Companion Teachers (GPK), regular teachers, regular students who are members of the Peer Friends Program, and ABK students. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman models. The validity of the data was tested through source triangulation and triangulation techniques. The results of the study show that the Peer Friends Program plays a positive role in supporting the social interaction of ABK students at SD Negeri 1 Losari, especially in the aspects of communication and social contact. ABK students are able to interact, although their interaction ability is still limited because they are influenced by their respective characteristics. However, the presence of peers increases the opportunity to interact in various school activities.